Integrated weed management in elephant foot yam cv. Gajendra - Upendra Kumar Naik; Padmakshi Thakur; Adikant Pradhan (JOURNAL OF ROOT CROPS, 2023)
The present investigation was undertaken at Shaheed Gundadhur College of Agriculture and Research Station, Indira Gandhi Krishi Vishwavidyalaya (IGKV), Jagadalpur, Chhattisgarh during 2019 and 2020 to assess the effect of different weed management practices in Amorphophallus cv. Gajendra. The experiment was laid out in RBD with three replications with eightdifferent treatments based on the individual or combination of pre emergence herbicide, post emergence herbicides, hand weeding, ground cover and control. Among the treatments T5 (Post-emergence herbicide at 30, 60 and 90 DAP) recorded the highest WCE (89.66%) followed by T4 (Hand weeding at 45 DAP + Post-emergence herbicide at 90 DAP) 88.92%. Significantly higher yield, corm weight per plant and per hectare were recorded in T5 treatment (Post-emergence herbicide at 30, 60 and 90 DAP) followed by T1 (Pre-emergence herbicide (1DAP) + Post-emergence herbicide at 45 and 90 DAP).